2005
DOI: 10.1111/j.1469-0691.2005.01145.x
|View full text |Cite
|
Sign up to set email alerts
|

Nocardiosis in a teaching hospital in the Central Anatolia region of Turkey: treatment and outcome

Abstract: Predisposing factors, antimicrobial susceptibility patterns, treatment and outcome were analysed for nine consecutive patients with nocardiosis. Predisposing factors were identified in six (67%) of the nine patients. Clinical syndromes of nocardial infection were pulmonary infection (three patients), cerebral infection (five patients) and disseminated infection (one patient). The predominant (60%) species was Nocardia farcinica rather than the Nocardia asteroides complex. Treatment was started empirically, mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
1
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 20 publications
5
44
1
4
Order By: Relevance
“…Recent reviews of collections of Nocardia clinical isolates by genotypic methods have found that a significant proportion, originally identified by routine phenotypic and chemotaxonomic methods, belong to a new species, Nocardia cyriacigeorgica (18,27,29,35). This species was first described in 2001 (38), and strains of N. cyriacigeorgica have since been recovered as the etiologic agent of human infection in Western Europe, Greece, Turkey, Japan, Thailand, and Canada (1,3,6,7,11,17,18,22,27,35,39). Most cases of infection have occurred in the context of human immunodeficiency virus-related or iatrogenic immune suppression.…”
mentioning
confidence: 99%
“…Recent reviews of collections of Nocardia clinical isolates by genotypic methods have found that a significant proportion, originally identified by routine phenotypic and chemotaxonomic methods, belong to a new species, Nocardia cyriacigeorgica (18,27,29,35). This species was first described in 2001 (38), and strains of N. cyriacigeorgica have since been recovered as the etiologic agent of human infection in Western Europe, Greece, Turkey, Japan, Thailand, and Canada (1,3,6,7,11,17,18,22,27,35,39). Most cases of infection have occurred in the context of human immunodeficiency virus-related or iatrogenic immune suppression.…”
mentioning
confidence: 99%
“…The incidence of human Nocardiosis is not well established in Turkey and comprises mostly case reports and small case series (Yildiz et al, 2005;Mentes et al, 2006;Elmaci et al, 2007;Arslan et al, 2007;Karakan et al, 2007). Pulmonary Nocardiosis is the most common presentation, with dissemination to other parts of the body, especially the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary Nocardiosis is the most common presentation, with dissemination to other parts of the body, especially the brain. Nine pulmonary and/ or cerebral Nocardiosis cases in humans (Yildiz et al, 2005) were defined on the basis of a positive culture and consistent clinical presentation in a retrospective study which performed at Erciyes University Teaching Hospital. Long term treatment of cases was started with ceftriaxone plus amikacin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogens can be found in environment, such as soil, decomposing vegetation, and other organic matter as well as in fresh and salt water. People with cancer or people taking steroid treatments are at risk for nocardiosis, and the infection often happens via several ways, such as inhalation (pulmonary nocardiosis), traumatic inoculation (cutaneous nocardiosis), and hospital-acquired (extra pulmonary nocardiosis) (204)(205)(206). In Turkey, a solitary case with granulomatous nocardial pleurisy was documented in a dog in Ankara (207).…”
Section: Dermatophilosis Is a Zoonotic Bacterial Infection Caused Bymentioning
confidence: 99%